HALAL INTEGRITY FROM LOGISTICS SERVICE PROVIDER PERSPECTIVE - Abdul Majid, Zawiah; Kamalrulzaman, Nitty Hirawaty; Abd Rahman, Azmawani; Jaafar, Harlina Suzana; Abdul Rahman, Nor Aida; Mohammad, Mohammad Fakhrulnizam (International Journal of Supply Chain Management, 2019)
In the complexity and dynamic supply chain network, understanding the integrity definition is paramount as to uphold Halal integrity from farm to fork to avoid miss-communication and fraudulent. This is because the perceptions of Halal integrity varied among the Halal food supply chain stakeholders due to the difference in scenario and perspectives. The authenticity and integrity of the Halal food supply chain are vital as it becomes the prerequisite in determining the potential business growth for sustainability. Consumers especially Muslim are concern about the integrity of Halal status of the food they consume as well as the product s origin. The purpose of this paper is to explain how LSP perceives Halal integrity in compliance to Halal Supply Chain Management System: MS2400.